The Effect of Purchase Regret and Dissatisfaction on Brand Switching Through Variety Seeking as an Intervening Variable - Adinda Najma Sidik; Nurul Komaryatin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of purchase regret and dissatisfaction on brand switching with variety seeking as an intervening variable. A quantitative approach was employed using Structural Equation Modeling (SEM) with 168 respondents selected through purposive sampling. The results indicate that purchase regret and dissatisfaction have a positive and significant effect on variety seeking and brand switching. Furthermore, variety seeking significantly influences brand switching and mediates the relationship between purchase regret and dissatisfaction on brand switching. These findings suggest that emotional factors and consumer dissatisfaction play an important role in driving variety-seeking behavior and brand switching.